2011
DOI: 10.3109/01676830.2011.558974
|View full text |Cite
|
Sign up to set email alerts
|

Enduragen Patch Grafts for Exposed Orbital Implants

Abstract: This consecutive case series suggests that Enduragen could be used as a safe and effective patch graft for exposed ocular implants. However, a larger prospective study with longer follow-up would be useful in further defining the indications and limitations of the Enduragen patch graft for the treatment of exposed orbital implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The ideal graft material should be adaptable to the socket surface, resistant to infection and easily epithelializing, provide scaffold to prothetic eye. Previously described materials for manage of exposed orbital implants include: dermis fat, temporalis fascia graft, frontal periosteum graft, tarsal patch ap, amniotic membrane graft, retroauricular myoperiostal graft or biosynthetic material patch graft as described by Enduragen [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal graft material should be adaptable to the socket surface, resistant to infection and easily epithelializing, provide scaffold to prothetic eye. Previously described materials for manage of exposed orbital implants include: dermis fat, temporalis fascia graft, frontal periosteum graft, tarsal patch ap, amniotic membrane graft, retroauricular myoperiostal graft or biosynthetic material patch graft as described by Enduragen [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported to repair orbital implant exposure by using banked sclera, frontal periosteum, amniotic membrane, müller muscle flap, or biosynthetic materials. 17,18 A good blood supply is essential for the survival of the graft, and for the supra-brow island flap pedicled with the orbicularis muscle, this was achieved with a good blood supply by the pedicled orbicularis muscle.…”
Section: Discussionmentioning
confidence: 99%
“…These complications are usually treated with drugs and secondary surgery (3)(4)(5). Orbital implant exposure is currently treated with various surgical techniques, including a dermal fat graft (6,7), acellular dermal graft (8), palate mucosal repair (9), oral mucosal repair (10), Enduragen ® graft repair (11), subconjunctival tissue flap repair (12) and fresh amniotic membrane repair (13). These surgical methods are unsatisfactory, however, as they cannot eliminate local inflammation or accelerate vascularization of the orbital implant.…”
Section: Introductionmentioning
confidence: 99%